Nationalisation of historical knowledge - Jaelani, Gani Achmad (Masyarakat Sejarawan Indonesia, 2018)
This research seeks to elaborate the attempts to nationalize the knowledge of the past in Indonesia between 1945 to 1965. This period is also known as the time when the new perspective in national history writing called indonesiasentris appeared. At that time, writing national history was a necessary to justify the direction of this new-born state. Accordingly, the so-called indonesiasentris which was known as the identity of Indonesian historiography, in spite of its contribution to the history as a science, supposes a uniformity of paradigm in national history writing. Far from being true, the indonesiasentris reflects the heterogeneity of the attempts to interpret the Indonesia’s past. This article will try to analyze the genealogy of the indonesiasentris as a concept; how this concept became the main focus of the debate after the Independence; to which extent this debate was influenced by that in global scale; lastly, this article will try to put in perspective the agenda of writing history in contemporary Indonesian historiography.